Photoluminescence of hexagonal ZnO nanorods hydrothermally grown on Zn foils in KOH solutions with different values of basicity - Nuengruethai Ekthammathat (2018)
Aligned hexagonal ZnO nanorods on pure Zn foils were hydrothermally synthesized in 30 mL solutions containing 0.05-0.50 g KOH. The products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and photoluminescence (PL) spectroscopy. In this research, wurtzite hexagonal ZnO nanorods grown along the [002] direction with green light emission at 541 nm caused by singly ionized oxygen vacancies inside were detected. © 2013 Nuengruethai Ekthammathat et al.